1999
DOI: 10.3171/jns.1999.90.5.0974
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of bilateral pallidotomy in the treatment of generalized dystonia

Abstract: This 29-year-old man with cerebral palsy complicated by generalized dystonia was treated by simultaneous bilateral posteroventral pallidotomy. Postoperatively, there was slow, but steady, improvement in the patient's dystonia and disability. However, the improvement in abnormal movements was only prominent for cervical dystonia and oromandibular dyskinesia. The patient's Burke-Fahn-Marsden dystonia scores were 51 preoperatively and 37, 33.5 and 33.5, at 3, 6, and 12 months postoperatively, respectively, demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 12 publications
(23 reference statements)
0
25
0
Order By: Relevance
“…Single spectacular results of PVP were mainly observed in primary dystonia (Iacono et al, 1996;Lozano et al, 1997). However, in secondary dystonia the results are not always positive (Lin et al, 1999a(Lin et al, , 1999bKhan et al, 2000). Signi®cant improvement has been reported for dystonia in the setting of progressive neurodegeneration such as Hallervorden±Spatz (Justesen et al, 1999) or Huntington's disease (Cubo et al, 1999), but in one detailed case report, this improvement appeared to be modest (Cubo et al, 2000).…”
Section: Pallidotomy For Dystoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Single spectacular results of PVP were mainly observed in primary dystonia (Iacono et al, 1996;Lozano et al, 1997). However, in secondary dystonia the results are not always positive (Lin et al, 1999a(Lin et al, , 1999bKhan et al, 2000). Signi®cant improvement has been reported for dystonia in the setting of progressive neurodegeneration such as Hallervorden±Spatz (Justesen et al, 1999) or Huntington's disease (Cubo et al, 1999), but in one detailed case report, this improvement appeared to be modest (Cubo et al, 2000).…”
Section: Pallidotomy For Dystoniamentioning
confidence: 99%
“…In recent years, with the renaissance of PVP for PD, pallidotomy was also rediscovered in the treatment of generalized dystonia (Iacono et al, 1995;Lozano et al, 1997;Shima et al, 1997;Lenz et al, 1998;Lin et al, 1998Lin et al, , 1999aLin et al, , 1999bOndo et al, 1998;Vitek et al, 1998;. For dierent reasons (dystonic postures incompatible with the stereotactic frame, reduced ability of children to cooperate during surgery, questionable intraoperative eects of stimulation on dystonia), surgery was partly performed under general anesthesia Ondo et al, 1998).…”
Section: Pallidotomy For Dystoniamentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 Pallidal surgery for dystonia has been reintroduced, and several studies with promising results have been published. [3][4][5][6][7] More recently, deep brain stimulation (DBS) through chronically implanted electrodes in the globus pallidus internus has gained increasing importance in the treatment of patients with medically intractable dystonia. [8][9][10][11] So far, however, most studies have reported only on relatively short follow up periods and are uncontrolled.…”
mentioning
confidence: 99%
“…Soon after the renewed interest for pallidotomy in Parkinson's disease, this procedure was applied to dystonia patients as well, with remarkable results, although the total number of patients reported is small [17,40,71,79]. Most patients were treated with bilateral pallidotomy and a consistent finding has been that patients with primary dystonia respond remarkably well, whereas patients with secondary dystonia do not improve much.…”
Section: Pallidotomy In Generalized Dystoniamentioning
confidence: 63%